Cascade Utilization of Flue Gas Waste Heat in Combined Heat and Power System with high Back-pressure (CHP-HBP). (December 2016) - Zhao, Shifei; Du, Xiaoze; Ge, Zhihua; Yang, Yongping
Abstract: In this study, the cascade utilization of the flue gas waste heat in CHP-HBP was performed. In the proposed system, flue gas of the coal-fired boiler and exhaust steam of the turbine were recovered synthetically. The maximum heat-supply capacity and the thermodynamic performance of the full heating period was analyzed. The results showed that: in the novel system, the maximum heat-supply capacity is 22.51 MW higher than that of reference system, and the coal consumption rate is reduced by 10.91g/kWh. Meanwhile, during the whole heating period, the gross electric power is 7.37 million kWh higher than the reference system.